Chronic Exercise Protects Against Cognitive Deficits in an Alzheimer’s Disease Model by Enhancing Autophagy and Reducing Mitochondrial Abnormalities - Morais, Gustavo Paroschi; de Sousa Neto, Ivo Vieira; Veras, Allice Santos Cruz [UNESP]; Teixeira, Giovana Rampazzo [UNESP]; Paroschi, Luciana Oliveira; Pinto, Ana Paula; dos Santos, Jonathas Rodrigo; Alberici, Luciane Carla; Cintra, Dennys Esper Corrêa; Pauli, José Rodrigo; Morelli, Ana Paula; Ropelle, Eduardo Rochete; et al. (Springer Nature, 2025)
Alzheimer’s disease (AD) is characterized by amyloid-β (Aβ) accumulation, autophagic lysosomal pathway (ALP) dysfunction, mitochondrial abnormalities, and neuroinflammation. Physical exercise (PE) protects against AD, but its molecular mechanisms remain unclear. We hypothesize that PE-mediated upregulation of REV-ERBα and TFEB pathways mitigates AD-related dysfunctions. Acute effects of FK506, a calcineurin inhibitor, were assessed as a TFEB suppressor in mice subjected to aerobic exercise. Chronic treadmill training (8 weeks, 4 sessions/week) was performed in APP/PS1 mice to evaluate hippocampal adaptations through functional tests, imaging, and molecular analyses. Acute FK506 administration inhibited Ppp3ca and Ppp3r1 expression without altering Tfeb levels. Chronic PE improved aerobic capacity, strength, coordination, and memory, promoted neuronal survival, and decreased Aβ levels in APP mice. It also elevated REV-ERBα protein and Nr1 d1 expression in wild-type and APP mice, increased ALP activity, and reduced abnormal mitochondria in the hippocampus of APP mice. A positive correlation between REV-ERBα and Nr1 d1 levels was observed in the 2-min NOR test. Public RNA-seq data revealed lower NR1D1 mRNA in extracellular vesicles from the human frontal cortex of AD patients compared to controls. PE prevents cognitive decline in APP/PS1 mice, enhancing memory, physical performance, and hippocampal health. These benefits are associated with ALP activation, mitochondrial improvements, and reduced neuroinflammation. REV-ERBα may mediate these protective effects, but further studies using pharmacological and genetic models are needed to confirm its role.